The curious case of Hemidactylus gujaratensis (Squamata: Gekkonidae) - Lajmi, Aparna; Datta-Roy, Aniruddha; Vyas, Raju; Agarwal, Ishan; Karanth, Praveen (Zootaxa, 2018)
Hemidactylus Oken, 1817 is one of the most speciose genera of the family Gekkonidae with more than 140 described species (Uetz et al. 2016). While this genus naturally occurs across the tropics and subtropics, a substantial part of its distribution also results from human-mediated dispersal. Carranza & Arnold (2006) retrieved five broad clades in a global phylogeny of Hemidactylus, one of which has species distributed in tropical Asia. Subsequent work by Bauer et al. (2010) and Bansal & Karanth (2010) revealed that the species from tropical Asia fell into two deeply divergent and potentially non-sister sub-clades—one comprising a large radiation confined to peninsular India and Sri Lanka (the Indian radiation, IR), and the other comprising species largely distributed in Southeast (SE) Asia.